Library Services for Off-Campus Business Professionals - Casey, Anne Marie (Journal of business & finance librarianship, 2002)
Central Michigan University has been offering degree programs to business professionals off-campus since 1971 through the College of Extended Learning. In 1976, Off-Campus Library Services was formed to provide library services exclusively for students enrolled in off-campus courses. This article describes the off-campus administration degree programs and the reference, instruction, and document delivery services that Off-Campus Library Services provides to these students.